The increasing role of subsidiary boards in MNCs: An empirical study - Kriger, Mark P. (Strategic Management Journal, 1988)
Abstract Little research has been done to date on the role of subsidiary boards (SBs) in MNCs. A two‐phase survey research design has yielded responses from 90 subsidiaries in 36 MNCs based in Europe, North America, and Japan. The sample provides evidence that: (1) SBs are perceived to be in transition from lesser to greater proactivity, and (2) MNCs with parent headquarters in North America, Europe, and Japan perceive the usefulness of these boards in different ways. The results indicate an increasingly active use of these boards in selective advisory and strategic roles. Some recommendations are presented for CEOs, chairmen, and subsidiary directors who are interested in designing their SBs to take better advantage of already legally mandated, but often underutilized, structures. SBs are not a panacea for resolving tensions between parents and subsidiaries and for monitoring changes in host country environments; however, they can provide added strategic governance for subsidiaries.